Thermal performance analysis in a parabolic trough solar collector with a novel design of inserted fins - Waleed Al-Aloosi; Yaser Alaiwi; Hudhaifa Hamzah (Case Studies in Thermal Engineering, 2023)
In this research, numerical simulations of turbulent flow in a modified parabolic trough solar collector with a novel design of inserted fins along the absorber tube was carried out. The clarity and purpose of incorporating fins into the absorber tube is to improve the efficiency of the heat transfer process. These fins were inserted as repeat sets, and each set has an increasing height of fins. The 3D simulations were conducted based on the finite volume approach utilizing the ANSYS FLUENT program. The obtained data are displayed in two different sections. In the first section, investigations were carried out to show the impact of the number of inserted fins on the thermal performance of the PTC. Five different models with two, three, four, five and six numbers of localized fins were analyzed and compared with the smooth reference model. The findings exhibit that the thermal performance of all modified models within the tested range of Re is greater than that of the reference model. Additionally, the sixth model with six fins has a maximum thermal performance of 1.4. In the second section, different cross-sectional areas of inserted fins including circular, elliptical and square were examined. For the sixth model, findings reveal that the maximum thermal performance for circular, elliptical and square cross-sectional fins is 1.4, 1.31 and 1.26, respectively, at Re=4000. Moreover, the Nu increased by almost 51% by changing the Re from 4000 to 8000 for the sixth model.